Volume 3a: 8th Design for Manufacturing Conference 2003
DOI: 10.1115/detc2003/dfm-48155
|View full text |Cite
|
Sign up to set email alerts
|

Manufacturability Evaluation Shell: A Re-Configurable Environment for Technical and Economic Manufacturability Evaluation

Abstract: The process of manufacturability evaluation is composed of a series of generic tasks. Though domain knowledge is utilized to evaluate manufacturability the evaluation method itself is independent of domain. Manufacturability has different levels of abstraction – process level, workshop level and machine level. Currently existing assessment tools address manufacturability in specific domains and stages. In the emerging markets of increasing competition, streamlining the PRP involves designing with manufacturing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
2
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Geometric reasoning technique has also been implemented in order to extract part definition from CAD model (Chen 1995;Dissinger 1996;Jacob 2004). Other techniques developed are 3D recognition model based on the design specifications of CAD model (Lu 1996;Horvath 1999;Chen 2001;Howard 2006), attribute extractor (Tharakan 2003), CAD modeller (Gebresenbet 2002) and data extraction from process simulation (Giachetti 2001;Giachetti 2005). The data obtained from a CAD model interprets the design details such as geometrical specifications and feeds the needed information to the system.…”
Section: Data Input Mechanismsmentioning
confidence: 99%
See 2 more Smart Citations
“…Geometric reasoning technique has also been implemented in order to extract part definition from CAD model (Chen 1995;Dissinger 1996;Jacob 2004). Other techniques developed are 3D recognition model based on the design specifications of CAD model (Lu 1996;Horvath 1999;Chen 2001;Howard 2006), attribute extractor (Tharakan 2003), CAD modeller (Gebresenbet 2002) and data extraction from process simulation (Giachetti 2001;Giachetti 2005). The data obtained from a CAD model interprets the design details such as geometrical specifications and feeds the needed information to the system.…”
Section: Data Input Mechanismsmentioning
confidence: 99%
“…It can be concluded that redesign suggestion is one of the major outputs of MAS that can assist designing products correctly with the helps of manufacturing information available at the design stage. • Machining such as milling (Venkatachalam 1993;Tharakan 2003), drilling (Venkatachalam 1993), electrochemical machining (Amalnik 1996), grinding (Jacob 2004), turning (Arezoo 2000), solid free-form fabrication process (e.g. stereolithography and selective laser sintering) (Gupta 2003); various conventional machining processes for metallic components fabrication such as milling, drilling, boring, grinding and broaching (Chan 2003).…”
Section: A Redesign Suggestionmentioning
confidence: 99%
See 1 more Smart Citation
“…Considerable emphasis in the literature has also been placed on environments for DFM. For example, generic domain independent shell was developed for manufacturability A repository for DFM problems evaluations that is configurable and customizable to virtually any domain or process (Tharakan et al, 2003). In contrast, our approach is to enable the reuse of previously formulated and solved DFM geometric tailoring problems, essentially capturing DFM knowledge in a set of high-level rules.…”
Section: Introductionmentioning
confidence: 99%
“…If we were to implement a complete geometric tailoring formulation and solution system, we would build on the work of Grewal and Choi (2005) and others. Reported DFM environments (Tharakan et al, 2003) typically have a qualitative reasoning and/or selection capability similar to ours, but not typically implemented using a logic-based formalism, as ours is.…”
Section: Introductionmentioning
confidence: 99%